Respuesta :
Answer:
T=-13
Step-by-step explanation:
Simplifying
5t + 12 = 4t + -1
Reorder the terms:
12 + 5t = 4t + -1
Reorder the terms:
12 + 5t = -1 + 4t
Solving
12 + 5t = -1 + 4t
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add '-4t' to each side of the equation.
12 + 5t + -4t = -1 + 4t + -4t
Combine like terms: 5t + -4t = 1t
12 + 1t = -1 + 4t + -4t
Combine like terms: 4t + -4t = 0
12 + 1t = -1 + 0
12 + 1t = -1
Add '-12' to each side of the equation.
12 + -12 + 1t = -1 + -12
Combine like terms: 12 + -12 = 0
0 + 1t = -1 + -12
1t = -1 + -12
Combine like terms: -1 + -12 = -13
1t = -13
Divide each side by '1'.
t = -13
Simplifying
t = -13
Answer:
t = -13
Step-by-step explanation:
5t + 12 = 4t - 1
In order to solve this equation, you first need to add 1, so that it cancels out -1 on the right side. Since there is a rule saying that whatever you do to one side, you need to do to the other, you have to also add 1 to 12, since you can't add 1 to 5t. So,
5t + 12 = 4t - 1
+1 +1
5t + 13 = 4t
Now, you need to combine like terms, which would be the t variables:
5t + 13 = 4t
-5t -5t
13 = -t
We cannot have the - sign in front of the t, so we have to divide each side by - in order to remove the - in front of the t
13 = -t
/- /-
t = -13